Lung adenocarcinoma diagnosed incidentally after renal biopsy for suspected right renal cancer. Issue 4 (6th April 2021) - Nepal, Sat Prasad; Shichijo, Takeshi; Ogawa, Yoshio; Nakasato, Takehiko; Nakagami, Yoshihiro; Morita, Jun; Oshinomi, Kazuhiko; Maeda, Yoshiko; Unoki, Tsutomu; Inoue, Tatsuki; Kato, Ryosuke; Amano, Satoshi; et al.
Abstract: We present a case of lung adenocarcinoma metastasizing to the right clear cell renal cell carcinoma diagnosed by computed tomography (CT)-guided renal biopsy and immunohistochemistry. A 72-year-old male patient had right lower abdominal pain for 3 days, followed by right loin pain for 10 days. On CT scan, renal cell cancer was suspected with multiple metastases. Renal cell cancer with metastatic lung adenocarcinoma was diagnosed on CT-guided renal biopsy with positive immunohistochemical markers. The patient, unfortunately, expired after few days of diagnosis. Tumor-to-tumor metastasis is an unusual disease, and its tumors are aggressive. A definite diagnosis of tumor-to-tumor metastasis is a clinical challenge. Immunohistochemistry helped us in the diagnosis without the primary lesion biopsy.